IMPLEMENTASI KURIKULUM MU’ADALAH (STUDI KASUS DI PONDOK PESANTREN RAFAH) - Manaf, Sofwan; Kurniawan, Muhammad Irfanudin; Muzakir, Muchammad Ibnu; Alfarisi, Muhammad Daffa Akbar (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to find out how the Mu’adalah curriculum is implemented at the Rafah Islamic boarding school, to find out what types of curriculums there are and the impact of the implementation of the Mu’adalah curriculum itself. The methodology used is a qualitative descriptive method by collecting data through interviews, observation and documentation. The informants in this research were the Director of Mu’adalah, Curriculum Staff, Santri Care, and teachers. The results of the research found that The implementation of the Mu’adalah curriculum at the Rafah Islamic boarding school does not only focus on intra-curricular activities, but also focuses on extra- curricular and co-curricular activities, and the impact of implementing the mu'dalam curriculum is that the mu'dalam curriculum is maximally integrated both intracurricular, extracurricular and co- curricular at the three educational centers, namely Islamic boarding schools as school education, family education and community education.